The Concept of Reciprocity in International Agreements:The Case of Indonesia and Singapore Extradition Treaty - Sulistiawati, Ratih; Afriani, Anita; Permata, Inda Mustika (JLAST : Journal of Law and Social Transformation, 2024)
Singapore is one of the main destinations for criminal offenders from Indonesia, which causes losses for Indonesia. In the process, in 2007 Indonesia signed an extradition agreement with Singapore but failed to be ratified. During Joko Widodo's administration in 2022, Indonesia re-signed an extradition agreement with Singapore along with the Defense Cooperation Agreement (DCA) and Flight Information Region (FIR). The three agreements also took effect simultaneously in 2024. Since its signing, it has taken 17 years for the extradition treaty between the two countries to come into force. This case is understood by the Principle of Reciprocity in International Law. This paper uses a qualitative research method with descriptive analytical research. In this case, reciprocity is one of the basic principles governing extradition treaties. This principle is crucial in negotiating fair and equal terms. In drafting international agreements, reciprocity can make negotiations more complex as each party may have different priorities and needs. This is reflected in the case of the extradition treaty between Indonesia and Singapore, where Indonesia wants this treaty to be ratified to facilitate the pursuit of criminals who have fled to Singapore and the return of assets that have been illegally taken. Singapore responded by asking Indonesia to ratify the DCA and FIR Agreement, which cover aspects of Singapore's broader defense and security interests. This principle is crucial in negotiating fair and equitable terms. Translated with DeepL.com (free version)